Production and catalytic upgrading of 2, 3-butanediol fermentation broth into sustainable aviation fuel blendstock and fuel properties measurement. (1st February 2023) - Affandy, Martin; Zhu, Cheng; Swita, Marie; Hofstad, Beth; Cronin, Dylan; Elander, Richard; Lebarbier Dagle, Vanessa
Graphical abstract: This study demonstrates the synthesis, conditioning, and catalytic upgrading of 2, 3-butanediol (BDO) fermentation broth into a jet fuel blendstock candidate. Highlights: 2, 3-butanediol (BDO) fermentation broth was synthesized at pilot scale. Aqueous BDO is converted into jet fuel via 4 steps: BDO → MEK → light olefins → oligomerized olefins → hydrogenation. Each step for catalytic upgrading of BDO fermentation broth into a jet fuel blendstock candidate was demonstrated. Jet fuel properties measurements demonstrate the process potential for production of sustainable aviation fuel. Abstract: With the increasing demand for sustainable supplies of aviation fuel and need to address climate change, new conversion technologies are needed to efficiently process biomass, produce high quality jet fuel blendstock, and meet carbon emission targets. This study demonstrates the synthesis, conditioning, and catalytic upgrading of 2, 3-butanediol (BDO) fermentation broth into a jet fuel blendstock candidate. A high-titer 2, 3-BDO fermentation broth (i.e., ∼90 g/L) was produced at a 100-L scale and pretreated via nanofiltration to decrease the impurities level in the broth from 4.6 to 0.6 wt%. A novel process for catalytic upgrading of aqueous 2, 3-BDO into a jet fuel blendstock candidate was developed, and each step was efficiently demonstrated. The catalytic steps include 1) 2, 3-BDO dehydration into methyl ethyl ketone (MEK) over AlPO4, 2) MEK conversion into olefins over Zn1 Zr10 Ox, 3) oligomerization of olefins over a zeolite beta, and 4) hydrogenation over platinum/carbon. Both the model feed and real 2, 3-BDO fermentation broth were tested for upgrading 2, 3-BDO to MEK. With the real feed, a continuous loss of conversion (i.e., >50 % loss over ∼140 h time-on-stream [TOS]) was partly attributed to reversible deactivation from coking species. However, the conversion remained stable with the model feed, which demonstrates the efficiency of the first step for converting aqueous 2, 3-BDO (10 wt% in water). For upgrading MEK to olefins, high selectivity to olefins (i.e., 82.5 %) was obtained at high conversion levels (i.e., 93–98 %) with stable conditions being achieved for > 70–hours TOS. Oligomerization of light olefins, which was demonstrated for > 270 h TOS, mainly led to the formation of dimers (C8-10 ) and trimers (C13 –14 ). The oligomerized product was hydrogenated and distilled to recover the jet fraction (35 mass% or 40.9 % carbon based yield), which consists mostly of desired isoalkanes (31.7 wt%), n -alkanes (24.5 wt%), and cycloalkanes (29.6 wt%). While some improvement is still needed to meet ASTM D7566 specifications for viscosity and final boiling point temperature, freezing point, density, aromatics content, and sulfur content of the jet blendstock candidate were within acceptable ranges, thus highlighting the potential of this process for production of jet fuel blendstock.